The Non-Fiction Picturebook: Knowing the World as an Integrated Experience - Giorgia Grilli (University of Bologna, 2022)
The new non-fiction picturebook for children is conceived not just as an informational book, but first and foremost as a beautiful object, characterized by a largely visual and proudly creative approach to knowledge. By blending information and artistic illustration/design, transmission of data and sophisticated aesthetic experimentation, this medium seems to bring successfully together the rational/explicit and the aesthetic/intuitive way of attending to the world, with promising consequences for the development of an integrated learning experience. Applying the findings of cognitive sciences to the analysis of non-fiction picturebooks can be enlightening to understand the full potential of such books in sharing knowledge with children. Their intrinsic multimodality and ability to stimulate different parts of the reader's brain makes them valuable in any educational context revolving around the paradigm of complexity and having connection (as opposed to disjunction) of different levels of experience as its aim.